Impact of Solvent Polarity on the Molecular Properties of Dimetridazole - Omer, Rebaz Anwar; Ahmed, Lana Omer; Koparir, Pelin; Hama, Jawameer (TUBITAK, 2022)
Recently molecular activity of dimetridazole (DMZ) gained interested due to medical applications. In this study, a computational investigation of the solvent impact on solvation free energy, dipole moments, polarizability, hyper-polarizability and characteristic atomic properties; hardness and softness quality, chemical potential, electronegativity and electrophilicity have been accounted for DMZ. All forms of the calculation for both gas phase and solution phase used Becke 3-Parameter of Lee-Yang parr (B3LYP) theory with a 631++G basis set. Using the Solvation Model on Density (SMD), the effect of solvent polarity on solvation free energy, dipole moment, polarizability, hyper-polarizability and molecular properties were measured. The dipole moment of the DMZ was lower value in a gas phase comparative with the solution phase. Furthermore, the electronegativity and chemical potential were increased from non-polar to polar solvents, while the electrophilicity index was decreased. However, in the case of chemical hardness & softness, the opposite relationship has been found. The results of this study contribute to an understanding of the molecular activity of DMZ and stimulate its activity in the solution phase. © 2022, TUBITAK. All rights reserved.
Çözücü Polaritesinin Dimetridazolün Moleküler Özellikleri Üzerindeki Etkisi
Keywords: Dimetrizole; Dipole moment; Molecule polarizability; Solvation model; Solvent-free energy